2018
DOI: 10.1080/17415993.2018.1485920
|View full text |Cite
|
Sign up to set email alerts
|

A convenient access to 1,2-diferrocenyl-substituted ethylenes via [3 + 2]-cycloelimination of 2-silylated 4,4,5,5-tetrasubstituted 1,3-dithiolanes

Abstract: After desilylation by treatment with TBAF, they are converted into the corresponding carbanions, which display different stability depending on the type of substituent. The presence of hetaryl and phenyl groups results in the exclusive formation of 1,2-diferrocenyl ethylenes. In contrast, the presence of methyl groups significantly enhances the stability of the carbanion, which by protonation yields trans -4,5-diferrocenyl-4,5-dimethyl-1,3-dithiolane. ARTICLE HISTORY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been pointed out that the addition of ferrocene residues in biologically active molecules offers the possibility of improving the efficacy of therapeutic drugs (Patra et al, 2017). In this connection, diferrocenyl-1,3dithiolane derivatives have pharmacological activity and may be considered as lead candidates for the development of new drugs or as building blocks for new molecules (Mloston ´et al, 2018).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…It has been pointed out that the addition of ferrocene residues in biologically active molecules offers the possibility of improving the efficacy of therapeutic drugs (Patra et al, 2017). In this connection, diferrocenyl-1,3dithiolane derivatives have pharmacological activity and may be considered as lead candidates for the development of new drugs or as building blocks for new molecules (Mloston ´et al, 2018).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Compared to aryl- and/or hetaryl-functionalized thioketones, their analogues bearing Fc-groups have received less attention despite the fact that the remarkable stability of the latter gives a good opportunity for their exploration in the current organic synthesis. In a series of recent publications we demonstrated that Fc-functionalized thioketones are attractive substrates for the synthesis of diverse Fc-containing S -heterocycles with variable ring size, e.g., thiiranes [18,19,20], 1,3-dithiolanes [21,22], 1,3-oxathioles [19] and 4 H -2,3-dihydrothiophenes [8,23]. One of the most spectacular applications is a recently reported protocol of a multi-step preparation of Fc-substituted ethylenes (ferrocifenes), known as the first organometallic anti-cancer agents [20].…”
Section: Introductionmentioning
confidence: 99%